Optimal Shunt Capacitor Sizing and Location on the Electrical Radial Distribution System with Microsoft Excel Solver - Nirukkanaporn, Vorasak; Triyangkulsri, Jittipath; Suksri, Amnart; Nethan, Cheiwchan (Engineering and Applied Science Research, 2013)
This paper presented the method of placing optimal shunt capacitor on the radial distribution system 22 kV to reduce power loss and to keep the constant level of voltage of system. The Microsoft Excel Solver is an Add-Ins of Microsoft Excel program that could analyze the data with the changing cells for optimized target cells. This method was developed by testing with two feeder modigications from the Provincial Electricity Authority (PEA) and compared the results to 2 tyoes the were the targets of minimized power loss and minimized rate of return, The results from the Microsoft Excel Solver were compared with the results from the power world program by the same data and condition The results from 2 methods were similar, therefore, the Microsoft Excel solver was efficient to solve the position placing capacitor problems as well as improvement on the quality of distribution system and reliability, The great benefit of the Microsoft Excel Solver is that it does not need to pay the license and the users could configure the condition of the program by themselves.